The Influence of Job Satisfaction and Citizenship Behavior (OCB) Organization on Employee Performance (Study On Small and Medium Enterprises of Restaurants in The Region Kambu District, Kendari City) - Sutrino, Anas (International Journal of Management and Education in Human Development, 2021)
This study aims to (1) determine the effect of Job Satisfaction on Employee Performance in Small and Medium Food Enterprises in Kambu District, Kendari City; (2) Knowing the effect of Organizational Citizenship Behavior (OCB) on Employee Performance in Small and Medium Food Enterprises in Kambu District, Kendari City; (3) Knowing the effect of Job Satisfaction and Organizational Citizenship Behavior (OCB) on Employee Performance in Small and Medium Food Enterprises in Kambu District, Kendari City. The object of this research is the employees of Small and Medium Food Enterprises in Kambu District, Kendari City who are included in the sample characteristics. Data was collected using questionnaires, observations and interviews. The sample in this study amounted to 116. The analytical method used is Multiple Linear Regression Analysis. The results of the study concluded that (1) Job Satisfaction had a positive and significant effect on Employee Performance in Small and Medium Food Enterprises in Kambu District, Kendari City; (2) Organizational Citizenship Behavior (OCB) has a positive and significant effect on employee performance at Small and Medium Food Enterprises in Kambu District, Kendari City; (3) the effect of job satisfaction and organizational citizenship behavior (OCB) either partially or simultaneously has a positive and significant effect on employee performance in small and medium food businesses in Kambu sub-district, Kendari city.